The show must go on: Dermatologic procedural education in the era of COVID-19 - Samara E. Pollock, BA; Neera R. Nathan, MD, MHS; Janelle S. Nassim, MD; A. Shadi Kourosh, MD, MPH; Kavita Mariwalla, MD; Sandy S. Tsao, MD (Wolters Kluwer, 2021)
COVID-19 procedural restrictions and concerns from both practitioners and patients have led to a decrease in cosmetic procedures performed. Reduced clinic space, the necessity of distancing between people, and patient preference for a smaller care team may restrict trainees from observing, assisting with, or performing procedures. Thus, trainees may be limited in their ability to learn, practice, and meet the required number of cases to achieve competence, subsequently necessitating a sustained demand for alternative methods of learning. In this review, we examine the efforts made thus far by both dermatologists and dermatology organizations to meet the educational procedural needs of trainees and compensate for limitations during the pandemic and highlight areas in which innovation may still be needed.